Phenotypic characterization of nosocomial isolates of Staphylococcus aureus with reference to MRSA - Bidya Shrestha; Bharat M. Pokhrel; Tribhuban M. Mohapatra (Journal of Infection in Developing Countries)
Background: Apart from being a major cause of mortality, nosocomial infections due to Staphylococcus aureus have been imposing a burden on patients, hospitals and health care systems. The present study was designed to determine the prevalence of methicillin resistant S. aureus (MRSA) among nosocomial isolates along with their phenotypic characterization. Methodology: MRSA and methicillin sensitive S. aureus (MSSA) were determined by performing four different tests viz: disc diffusion, oxacillin screen agar test, MRSA latex agglutination test, and MIC of oxacillin by E test. Results: Of the 149 S. aureus nosocomial isolates, 44.9% were MRSA, which included 82.1% of homogeneous MRSA and 17.9% of heterogeneous MRSA. Association of MRSA infection was found to be significantly higher in skin and lower respiratory tract infections. Of the MRSA isolates, 65 were multiresistant oxacillin resistant Staphylococcus aureus (MORSA) and 2 were nonmultiresistant oxacillin resistant Staphylococcus aureus (NORSA). D tests performed on 136 isolates showed that Inducible macrolide-lincosamide-streptogramin B (MLSB) and constitutive MLSB resistance were found to be associated with MRSA. On the contrary, susceptibility to both erythromycin and clindamycin was found to be associated with MSSA. However, MSB (macrolide-streptogramin B) resistance was not found associated either with MRSA or MSSA. Furthermore, both inducible and constitutive MLSB were found to be associated with only homogenous MRSA. Conclusion: D tests may be made mandatory in all S. aureus isolates as inducible MLSB resistance cannot be detected in routine susceptibility test unless erythromycin and clindamycin are placed 15-26 mm apart.